2016
DOI: 10.3892/mmr.2016.5872
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of dieckol on hypoxia-induced epithelial-mesenchymal transition of HT29 human colorectal cancer cells

Abstract: Hypoxia-induced epithelial-mesenchymal transition (EMT) has been identified as essential for tumor progression and metastasis. The present study examined the effects of an antioxidant, dieckol, on hypoxia-induced EMT in HT29 human colorectal cancer cells. HT29 cells were treated with a hypoxia-inducing agent, CoCl2, and an increase in the levels of intracellular reactive oxygen species (ROS) and various morphological changes, such as loss of cell-cell contact and aggressive cell migration were observed. CoCl2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Dieckol treatment reversed ROS levels and restored EMT-related morphological changes, suggesting that dieckol is a potential therapeutic for metastatic colorectal cancer. 160 In line with this finding, another study showed that CoCl 2 could initiate EMT in breast cancer cells. Tetraethylenepentamine (TEPA), a copper chelator, was capable of inhibiting CoCl 2 -induced ROS accumulation and EMT progression.…”
Section: Targeting Redox-regulated Emt For Cancer Therapymentioning
confidence: 68%
“…Dieckol treatment reversed ROS levels and restored EMT-related morphological changes, suggesting that dieckol is a potential therapeutic for metastatic colorectal cancer. 160 In line with this finding, another study showed that CoCl 2 could initiate EMT in breast cancer cells. Tetraethylenepentamine (TEPA), a copper chelator, was capable of inhibiting CoCl 2 -induced ROS accumulation and EMT progression.…”
Section: Targeting Redox-regulated Emt For Cancer Therapymentioning
confidence: 68%
“…Therefore, suppression of invasion and metastasis of cRc cells may contribute to improvement of the treatment of this illness. Multiple genes and signaling pathways are important in the progression of cRc (5)(6)(7)(8)19,20), including various members of the ANXA family. Zhang et al (21) demonstrated that non-steroid anti-inflammatory drugs affect the activity of the nuclear factor-κB signaling pathway resulting in ANXA1 inhibition, which may lead to growth suppression of cRc cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, a high proportion of cRc patients were diagnosed in the advanced stage (2), which resulted in poor prognosis and recurrence or metastasis even after treatment. Multiple genes are responsible for this process (3)(4)(5)(6)(7)(8); however, the molecular mechanism remains unclear. Therefore, identifying novel genes is considered to be vital for analyzing pathophysiological variations, evaluating medical conditions and defining novel targets in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Since an increase in ROS had been previously implicated in EMT induction in different cells, [18][19][20][21] we hypothesized that the reduction in ROS levels induced by the compounds could be leading to changes in the metastatic ability of H4 cells. The effect of FeL and CuL on the migration of H4 cells was thus investigated by the transwell migration assay.…”
Section: Fel and Cul Complexes Reduce Migration Through Inhibition Ofmentioning
confidence: 99%
“…17 Interestingly, the EMT process seems to be connected to cellular ROS levels and different metals have been shown to induce EMT in different cancers through a ROSdependent mechanism. [18][19][20][21] As such, modulation of ROS levels in cancer cells has been put forth as another promising strategy to tackle the problem of local invasiveness and metastization of cancer. 22 One possible strategy to modulate the levels of cellular ROS, and, consequently, the cancer cells metastatic ability, is the use of metal-based compounds that mimic the superoxide dismutase (SOD) and catalase (CAT) enzymes, important cellular antioxidant proteins that are responsible for maintaining the cellular redox balance.…”
Section: Introductionmentioning
confidence: 99%